Austria : Financial Sector Assessment Program Update Technical Note; Factual Update and Analysis of the Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This technical note highlights the financial sector assessment program update of Austria with factual update for effective banking supervision. Financial sector regulation and supervision should be conducted in the general public interest. Although authorities have acted effectively in recent cases of major problems, it is recommended that, within the legal framework in place, a set of practical provisions and procedures be elaborated for an orderly exit in case of failures and other stress situations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet